2020
DOI: 10.1186/s13059-020-02169-y
|View full text |Cite
|
Sign up to set email alerts
|

An integrated peach genome structural variation map uncovers genes associated with fruit traits

Abstract: Background Genome structural variations (SVs) have been associated with key traits in a wide range of agronomically important species; however, SV profiles of peach and their functional impacts remain largely unexplored. Results Here, we present an integrated map of 202,273 SVs from 336 peach genomes. A substantial number of SVs have been selected during peach domestication and improvement, which together affect 2268 genes. Genome-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 74 publications
9
89
1
Order By: Relevance
“…2b). Gene expression pattern was consistent with their genotypes, as fruit abortion trait was recessive [6,8]. As well, tissue speci c analysis showed that this gene was mostly expressed in seed and fruit ( Fig.…”
Section: Identi Cation and Expression Analysis Of Ppsnrk1γsupporting
confidence: 66%
See 3 more Smart Citations
“…2b). Gene expression pattern was consistent with their genotypes, as fruit abortion trait was recessive [6,8]. As well, tissue speci c analysis showed that this gene was mostly expressed in seed and fruit ( Fig.…”
Section: Identi Cation and Expression Analysis Of Ppsnrk1γsupporting
confidence: 66%
“…In order to elucidate the genetic basis for at fruit abortion, candidate gene identi cation was carried out. We have already identi ed a 1.67-Mb chromosome inversion co-segregated with at fruit shape and validated it in 336 peach accessions [8] (Fig. 2a).…”
Section: Identi Cation and Expression Analysis Of Ppsnrk1γmentioning
confidence: 60%
See 2 more Smart Citations
“…Likewise, GWAS based on the graph soybean pan-genome identified a PAV associated with variation in seed luster [ 24 ]. In peach, candidate causative SVs for early fruit maturity, flesh color around the stone, fruit shape, and flat shape formation have also been observed [ 121 ]. However, our understanding of the importance of SVs to phenotypic trait variation is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%